Carbon footprint measurement in the sustainability of seafood - Pincay Cantos, María Fernanda (2021)
Climate change is one of the greatest environmental challenges that today’s society must face. Various human activities, such as transport, the agricultural sector, industrial processes, among others, are releasing large amounts of greenhouse effect gases (GHG) into the atmosphere, the most important of which is CO2. The objective was to measure the carbon footprint of one of the seafood products of the Ecuadorian agri-food export sector, such as cooked tuna. The carbon footprint is a parameter that represents the total GHG emissions, expressed in CO2e mass, generated directly or indirectly by a product, service, organization or event throughout its life cycle. The calculation was made using a cradle-to-door approach, including GHG emissions generated from the search and capture of tuna in the fishing phase until its distribution to the port of the exporting country, using the methodology PAS 2050, contemplating four stages: tuna fishing, tuna processing, product packaging, distribution of packaged tuna to the port of destination; obtaining a global result of 6.32 kg CO2e·kg-1 of tuna, pretending that the calculation made becomes a reference, facilitating more effective emission reduction policies, in the company and in the country.